2008
DOI: 10.1016/j.conbuildmat.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Properties of cementless mortars activated by sodium silicate

Abstract: The present paper reports the testing of twelve alkali-activated mortars and a control ordinary portland cement (OPC) mortar. The main aim is to develop cementless binder activated by sodium silicate powder. An alkali quality coefficient combining the amounts of main compositions of source materials and sodium oxide (Na 2 O) in sodium silicate is proposed to assess the properties of alkali activated mortars, based on the hydration mechanism of alkali-activated pastes. Fly ash (FA) and ground granulated blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(94 citation statements)
references
References 13 publications
5
87
0
2
Order By: Relevance
“…Yang et al [39] reported that the initial flow of an alkali activated mortar decreased with an increase of Na 2 O content when they used sodium silicate powder as an activator. Yang and Song [40] used sodium silicate powder and sodium hydroxide powder to produce AAS mortars.…”
Section: Mini Slumpmentioning
confidence: 99%
“…Yang et al [39] reported that the initial flow of an alkali activated mortar decreased with an increase of Na 2 O content when they used sodium silicate powder as an activator. Yang and Song [40] used sodium silicate powder and sodium hydroxide powder to produce AAS mortars.…”
Section: Mini Slumpmentioning
confidence: 99%
“…Ground Granulated Blast furnace slag, a by product obtained from the steel industries is a glassy, granular, non metallic material consisting essentially of silicates and aluminates of calcium and other bases. Addition of GGBFS is said to enhance geopolymerisation and increase the compressive strength mix [ [19][20][21][22][23], Ambily (2011Ambily ( ,2012]. Moreover GGBFS proves to be an effective binder to produce better quality than Ordinary Portland Cement concrete (OPC) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 14 . Sodium hydroxide powder was also added in groups I and II to control the molar ratio (SiO 2 /Na 2 O) of the sodium silicate at the same Na 2 O/SM ratio.…”
Section: Designmentioning
confidence: 99%
“…Yang and Song 14,16 showed that the compressive strength development of GGBS-based AA mortar according to age could be modeled using the formula recommended by ACI 209 17 as follows:…”
Section: Compressive Strength Developmentmentioning
confidence: 99%
See 1 more Smart Citation